2022
DOI: 10.4236/jssm.2022.154024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Management of Public Private Partnerships for the Provision of Affordable Housing in Nigeria

Abstract: The Impact of Public Private Partnership is beginning to be more pronounced in emerging markets like Kenya and Nigeria as a preferred means for the delivery of Infrastructure and Housing. In terms of its popularity, the adoption and growth of Public private partnerships has been traced to under performance of Government Budgeting and lack of sufficient funding available to government for financing the different strategically important and development focused projects (including Social Housing), this is also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In line with this, it was reported by Alrashidi (2021) that the private sector's competitive pressures ensure quality delivery of public services as they might be better able to manage risk associated with projects than the public sector. Others also revealed that PPP arrangement allows public institutions to benefit from the special technical expertise of the private sector, manage issues, and realize cost savings (Owolabi et al, 2019;Ibrahim, 2022;Owotemu et al, 2022). It is therefore important for the government to factor in occupiers' satisfaction into the project's goals of PPP in order to justify these reasons for the adoption of PPP procured housing projects in Kebbi State.…”
Section: Rii Results On the Reasons For The Adoption Of Ppp Procured ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, it was reported by Alrashidi (2021) that the private sector's competitive pressures ensure quality delivery of public services as they might be better able to manage risk associated with projects than the public sector. Others also revealed that PPP arrangement allows public institutions to benefit from the special technical expertise of the private sector, manage issues, and realize cost savings (Owolabi et al, 2019;Ibrahim, 2022;Owotemu et al, 2022). It is therefore important for the government to factor in occupiers' satisfaction into the project's goals of PPP in order to justify these reasons for the adoption of PPP procured housing projects in Kebbi State.…”
Section: Rii Results On the Reasons For The Adoption Of Ppp Procured ...mentioning
confidence: 99%
“…Therefore, Ibrahim (2022) emphasized that the implementation of risk management in PPP housing projects in Nigeria is very important to the survival of the building industry and there is need for measures in order to improve the practice towards effective housing provision. In the contribution of Owotemu et al (2022), it was established that PPP arrangement allows public institutions to benefit from the special technical expertise of the private sector, manage issues, and realize cost savings. Under PPP, private contractors usually have no relationship with the end user, and all financial interactions are conducted with the public sector partner.…”
Section: Reasons For Adopting Public-private Partnership (Ppp) System...mentioning
confidence: 99%
See 1 more Smart Citation
“…Public-Private Partnership (PPP) is a collaborative model for public infrastructure management that involves a strategic alliance between government entities and private sector organizations. In the PPP framework, the government and private entities enter into contractual agreements to jointly design, finance, implement, and operate public infrastructure projects (Owotemu, Daniel, & Abubakar, 2022). This approach leverages the strengths of both sectors: the public sector's role in policy-making, regulation, and service provision, and the private sector's efficiency, innovation, and access to capital.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches enhance housing outcomes by involving stakeholders but require more time and resources. Recommendations include feasibility studies, capacity building, policy development, and trust-building mechanisms(Owotemu et al, 2022;Kavishe & Chileshe, 2019;Ogunbayo et al, 2021;Eseoghenea et al, 2022).…”
mentioning
confidence: 99%